Experimental study and finite element analysis of energy dissipating outriggers. Issue 8 (August 2017) - Yang, Qingshun; Lu, Xinzheng; Yu, Cheng; Gu, Donglian
The outriggers are widely adopted in tall and super-tall buildings. Their energy dissipation capacity can significantly influence the nonlinear seismic responses of the entire building structure. Based on an actual tall building project, the structural responses and energy dissipation capacities of three different outriggers were studied through experiments and finite element analyses. The test results of conventional outrigger specimen showed a steep deterioration after peak strength and an unfavorable energy dissipation capacity due to the global buckling of the braces and the local buckling of the chords after flexural yielding. Using buckling-restrained braces and reduced beam sections in a new design of the outriggers, the energy dissipation capacity and the ductility of the outriggers were significantly improved. The yield and peak strengths were further improved with the use of high-strength steel in chords on a third specimen. The finite element simulation of the three specimens indicated that the initial imperfection of the specimens shall be considered, and the developed finite element models yielded good agreements with the test results. The outcome of this work can provide additional references for the application of the outriggers in tall buildings.